Active principles of Tetradenia riparia. IV. Anthelmintic activity of 8(14), 15-sandaracopimaradiene-7α, 18-diol. (24th April 2018) - Van Puyvelde, Luc; Liu, Maoxuan; Veryser, Cedrick; De Borggraeve, Wim M.; Mungarulire, Joseph; Mukazayire, Marie Jeanne; Luyten, Walter
Abstract: Ethnopharmacological relevance: Tetradenia (T.) riparia (Hochst.) Codd (Lamiaceae), formerly known as Iboza riparia (Hochst.) N.E.Br., is one of the most frequently used medicinal plants in traditional Rwandese medicine. It was used as a remedy against a wide range of diseases including malaria, angina, yaws, dental abscesses, headache, worm infections and several kinds of fevers and aches. Aim of the study: This study aims to identify the compounds active against helminths from Tetradenia riparia . Methods: A bioassay-guided isolation of anthelmintic compounds from the leaves of Tetradenia riparia was performed using a Caenorhabditis elegans ( C. elegans ) testing model. Results: The bioassay-guided isolation led to one active compound, i.e. 8(14), 15-sandaracopimaradiene-7α, 18-diol. Its IC50 value was 5.4 ± 0.9 µg/mL (17.8 ± 2.9 µM). Conclusions: We identified the bioactive compound from Tetradenia riparia responsible for its anthelmintic activity: 8(14), 15-sandaracopimaradiene-7α, 18-diol. Although the compound and several of its bioactivities have been described before, this is the first report of its anthelmintic effect.